Rethinking the University of Maryland Authority File for the Linked Data Environment. Issue 1 (3rd April 2019) - Parker, Bria; Gray, Adam
Abstract: The development and implementation of a new digital collections system built on the Linked Data Platform has provided University of Maryland Libraries with an ideal opportunity to prototype and test ways to model local corporate name authorities in resource description framework (RDF). This includes assessing the local corporate names metadata, reconciling these names against existing authorities, and devising and executing an RDF model for unreconciled names in support of the new linked data environment.